The Impact of Detention on Youth Outcomes: A Rapid Evidence Review. (October 2021) - Gilman, Amanda B.; Walker, Sarah Cusworth; Vick, Kristin; Sanford, Rachael
While there is ample research examining the short- and long-term effects of juvenile incarceration (broadly defined), less is known about the specific consequences of the most common form of youth incarceration, juvenile detention. We conducted a Rapid Evidence Review (RER), limiting our search to the past 10 years to include studies that captured modern juvenile justice practices, to assess the body of literature evaluating the effects of juvenile detention on youth outcomes. Our initial search yielded over 1, 800 articles, but only three ultimately met criteria for inclusion in our review. We conclude that there is a profound lack of research regarding the consequences of juvenile detention, an issue that affects a large number of youth in the United States.